2022
DOI: 10.1186/s12903-022-02430-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, FEM analysis and experimental validation of tooth movement prediction model of orthodontic archwire T-loop

Abstract: Background The T-loop has been used clinically to close gap between teeth. And it is a typical orthodontic archwire bending method. However, the design of the T-loop parameters for different patients is based on the clinical experience of the dentists. The variation in dentists' clinical experience is the main reason for inadequate orthodontic treatment, even high incidence of postoperative complications. Methods Firstly, the tooth movement prediction model is establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Interestingly, one study that determined the multi‐bite OT with three consecutive closures to MIP reported mean values of 0.14−0.17 s in a general population with healthy dentitions or after the retention period of orthodontic treatment 19 . Studies assessing OT with a single bite have reported mean values of 0.21−0.70 s in a similar population 23,28,39,40 . Thus, current research data suggest that the OT is longer with single‐bite closure compared with multi‐bite or consecutive closures to MIP.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, one study that determined the multi‐bite OT with three consecutive closures to MIP reported mean values of 0.14−0.17 s in a general population with healthy dentitions or after the retention period of orthodontic treatment 19 . Studies assessing OT with a single bite have reported mean values of 0.21−0.70 s in a similar population 23,28,39,40 . Thus, current research data suggest that the OT is longer with single‐bite closure compared with multi‐bite or consecutive closures to MIP.…”
Section: Discussionmentioning
confidence: 74%
“…19 Studies assessing OT with a single bite have reported mean values of 0.21−0.70 s in a similar population. 23,28,39,40 Thus, current research data suggest that the OT is longer with single-bite closure compared with multi-bite or consecutive closures to MIP.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation